THE PRODUCTION OF PHOSPHOLIPID CONCENTRATES FROM SAFFLOWER OIL - V. N. Vasilenko; L. N. Frolova; I. V. Dragan; N. A. Mikhailova; S. Altai; T. S. Altayev (Современная наука и инновации)
The relevance of the development of the production of domestic phospholipid additives is determined by the high demand for phospholipids in the production of many food products, complex dietary supplements and pharmaceuticals; discrediting a number of imported phospholipid products obtained from genetically modified soybean seeds; the practical lack of domestic technologies for the production of phospholipid additives focused on the industrial use and use of domestic safe raw materials. In this regard, the goal was set - the development of import-substituting technology for the production of lecithin from phospholipid concentrates of safflower oils.